Recent studies on human platelets-galectin-1 interactions - González, Mariana Marta (2009)
Animal lectins are proteins that have the ability to bind monosaccharide or oligosaccharide carbohydrates. They were classified into five families according to their primary structure. Galectins, one of the members of this group, were previously known as S-type lectins or S-Lac. The galectin family is a phylogenetically conserved lectin family which shared amino acid sequences and a carbohydrate recognition domain. All galectins bind lactose and other β-galactosidic oligosaccharides. Fifteen mammalian galectins have been identified, being designated as Gal-1 to Gal-15. We have previously demonstrated that porcine spleen Gal-1 interacts with resting human platelets and after activation with thrombin (Tr) demonstrating the presence of receptors, a necessary condition in order to exert functional roles. The discovery of endogenous Gal-1 and their potential ligands/receptors, suggest an autocrine mechanism acting in HPlt (human platelets) to produce different functional roles. The information available is very poor which demonstrates the need to deep other aspects, some of which have already been addressed (localization and ultrastructural changes, protein associations and platelet receptors) and other are pending, as its relevance in platelet physiopathology, in particular its association with thrombotic and inflammatory processes.